2007
DOI: 10.2118/07-11-ge
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Commercial In Situ Combustion Projects Worldwide

Abstract: Picture of Alex Turta (Available In Full Paper) Alex Turta is a project leader for Improved Oil Recovery at Alberta Research Council (ARC) in Calgary. His research interests include primary recovery of heavy oils, waterflooding of light oils, and thermal recovery methods for heavy oil. He has extensive experience of heavy oil exploitation, from laboratory to field pilots, and has undertaken international consultancy for thermal pilot evaluation. He assisted in the development of the enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 2 publications
0
53
0
Order By: Relevance
“…Balol and Santhal oilfield were discovered in 1971 in the northern part of Gujarat. The production was started in 1971 on Santhal and in 1985 on Balol oilfield (Turta et al 2007). This project is initiated at Balol field (Gujarat) on pilot scale and later, the project is expanded to commercial scale at Balol and Santhal field, Gujarat (Chattopadhyay et al 2003;Chattopadhyay et al 2004).…”
Section: Eor Techniques In Indian Reservoirsmentioning
confidence: 99%
“…Balol and Santhal oilfield were discovered in 1971 in the northern part of Gujarat. The production was started in 1971 on Santhal and in 1985 on Balol oilfield (Turta et al 2007). This project is initiated at Balol field (Gujarat) on pilot scale and later, the project is expanded to commercial scale at Balol and Santhal field, Gujarat (Chattopadhyay et al 2003;Chattopadhyay et al 2004).…”
Section: Eor Techniques In Indian Reservoirsmentioning
confidence: 99%
“…It is also interested in hydrogen generation by ISC process from an oil sands reservoir (Kapadia et al, 2011) [3] . However, it has been reported that just four ISC projects have been carried out in the world (Turta et al, 2007) …”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are four active commercial ISC projects in the world (Turta et al 2007). The maximum oil production from commercial ISC projects has been decreasing from 5100 m 3 /day (32,000 bbl/day) in 1992-2400 m 3 /day (15,000 bbl/day) in 2004 (Turta et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are four active commercial ISC projects in the world (Turta et al 2007). The maximum oil production from commercial ISC projects has been decreasing from 5100 m 3 /day (32,000 bbl/day) in 1992-2400 m 3 /day (15,000 bbl/day) in 2004 (Turta et al 2007). Despite the number of difficulties that ISC projects have encountered in the past, they continue to maintain an appeal to the petroleum community, arising from the technical efficiency, environmental sustainability, and economic attractiveness of the process.…”
Section: Introductionmentioning
confidence: 99%